2020
DOI: 10.1213/ane.0000000000004221
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Isoelectric Electroencephalography Events in Infants and Young Children Undergoing General Anesthesia

Abstract: BACKGROUND: In infants and young children, anesthetic dosing is based on population pharmacokinetics and patient hemodynamics not on patient-specific brain activity. Electroencephalography (EEG) provides insight into brain activity during anesthesia. The primary goal of this prospective observational pilot study was to assess the prevalence of isoelectric EEG events—a sign of deep anesthesia—in infants and young children undergoing general anesthesia using sevoflurane or propofol infusion for maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 22 publications
0
28
2
Order By: Relevance
“…Several studies in older adults have shown that intraoperative burst suppression under GA is associated with an increased risk of postoperative cognitive dysfunction. [18][19][20] Though burst suppression occurs in children under multiple modalities of GA 21 at a rate of approximately 50%-60%, [22][23][24] potential consequences of this remain unknown. Our data collection to date does not show any evidence of burst suppression after administration of SA in infants, suggesting SA may be associated with less risk for this pattern of brain activity and any potential morbidities therefrom.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in older adults have shown that intraoperative burst suppression under GA is associated with an increased risk of postoperative cognitive dysfunction. [18][19][20] Though burst suppression occurs in children under multiple modalities of GA 21 at a rate of approximately 50%-60%, [22][23][24] potential consequences of this remain unknown. Our data collection to date does not show any evidence of burst suppression after administration of SA in infants, suggesting SA may be associated with less risk for this pattern of brain activity and any potential morbidities therefrom.…”
Section: Discussionmentioning
confidence: 99%
“…The patients who received propofol boluses had more possibilities to develop burst suppression, which may be attributed to the administration of high doses of propofol to achieve deeper anesthesia and adapt the level of nociceptive stimulation during surgery. Administration of an additional propofol bolus, either before or after intubation, can result in either enhancement of the slow oscillation or the conversion of the slow oscillation into burst suppression 7,24 . Overall, propofol boluses, use of sevoflurane, and lower arterial pressure during anesthesia were associated with burst suppression events.…”
Section: Discussionmentioning
confidence: 95%
“…In a recent study in children 0–37 months of age requiring general anesthesia for noncardiac or intracranial surgery using sevoflurane or propofol infusion, in 63% of the patients, an episode of isoelectricity was observed, more related to high ASA status patients [ 60 ].…”
Section: Pharmacologymentioning
confidence: 99%